2017
DOI: 10.4103/0976-237x.205064
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparative evaluation of cleaning efficacy and volumetric filling in primary molars: Cone beam computed tomography evaluation

Abstract: Introduction:Pulpectomy of primary teeth is mostly carried out with hand files and broaches which is tricky and time consuming procedure. The development of new design features like varying tapers, non-cutting safety tips and varying length of cutting blades have resulted in new generation of rotary instruments.Aim:To compare and evaluate cleaning efficacy, canal preparation and volumetric filling using conventional files and rotary V Taper files through cone beam computed tomography.Materials and Method:Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The majority of laboratorial studies have employed ZOE as the gold standard obturation material, evaluating different filling techniques or different obturation materials on an isolated approach. Some studies used radiographs as evaluation method, resulting only in a bidimensional interpretation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of laboratorial studies have employed ZOE as the gold standard obturation material, evaluating different filling techniques or different obturation materials on an isolated approach. Some studies used radiographs as evaluation method, resulting only in a bidimensional interpretation .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used radiographs as evaluation method, resulting only in a bidimensional interpretation . Others used spiral CT scans or cone beam CT which also allows a tridimensional interpretation, but with very low resolution and image quality compared with micro‐CT. The use of the micro‐CT, a high‐resolution non‐destructive method, allows quantification and localization of the voids along the root canal and a tridimensional evaluation of the quality of the filling, by allowing a detailed quantification of the percentage volume of filled canals …”
Section: Discussionmentioning
confidence: 99%
“…30 Although there is a study which found no significant difference in terms of apical sealing quality between ProTaper, Mtwo rotary instruments and K-type files 31 , most studies reported that filling density and sealing quality were higher when the tooth preparation was performed using the rotary instruments or the hybrid method. 24,30,32,33 The Mtwo rotary instrument system was reported to show better sealing and higher filling volume in a study comparing Mtwo and K-type files, although, gaps were observed in the canals of the two groups after filling. 32 Although apical leakage was observed in all deciduous teeth prepared with Hero642, Race, Mtwo, ProTaper rotary instruments and K-type files, the highest leakage value occurred with Ktype files.…”
Section: Rotary Instruments Used In Root Canal Therapiesmentioning
confidence: 99%
“…The hybrid method was reported to clean smears and debris better and to create more successful canal filling with better shaping. 17,24 Rotary instruments working with reciprocal movements such as Reciproc and WaveOne were shown to provide more successful cleansing compared to rotary instruments working with rotation movement and were recommended to be used for deciduous teeth. 16,25 In conclusion, the studies comparing the cleansing efficacies of rotary instruments and stainless steel files revealed no statistically significant difference between the two methods.…”
Section: Rotary Instruments Used In Root Canal Therapiesmentioning
confidence: 99%
“…However the usage of rotary instrumentation in the field of pediatric dentistry was able to shortening the treatment time and to reduce the fatigue of patient and professional. Furthermore, it was also possible to achieve a high quality biomechanical preparation, which results in uniform and more predictable obturations as well as high degree of cleanness (Pinheiro et al, 2012;Musale & Mujawar, 2014;Katge et al, 2014;Ramanazi et al, 2016;Deshpande, Joshi & Naik, 2017), due to the tapered shape, which leads to a better root filling (Barr, Kleier & Barr, 2000;George et al, 2016;Deshpande, Joshi & Naik, 2017). These aspects assure its usage in pediatric dentistry, since time is key to properly manage the child behavior during the procedure (George et al, 2016;).…”
Section: Introductionmentioning
confidence: 99%